A first account of Chyromyidae (Diptera: Acalyptratae) from continental Central and South America and some Caribbean Islands, with descriptions of new species - Ebejer, Martin J. (Zootaxa, 2023)
An account of Neotropical Chyromyidae is given and the following new species are described: Gymnochiromyia semihirta sp. nov., G. tropica sp. nov., Tethysimyia bonairensis sp. nov., T. chilensis sp. nov., T. litophila sp. nov. and T. nigrifacies sp. nov. Aphaniosoma Becker and Notiochyromya Ebejer are reported for the first time from the Neotropical Region. The following species are transferred from Aphaniosoma Becker to Tethysimyia Ebejer: Tethysimyia arenicola (Wheeler, 1994) comb. nov., Tethysimyia aldrichi (Wheeler, 1961) comb. nov., T. galamarilla (Wheeler, 1994) comb. nov., T. macalpinei (Hardy, 1980) comb. nov. and T. minuta (Hardy, 1980) comb. nov., T. rabida (Wheeler, 1994) comb. nov. A key to the Neotropical species of Tethysimyia is provided.